Behavior of chromogenic pigments and influence of binder in organic smart coatings. (January 2021) - Rossi, Stefano; Simeoni, Matteo; Quaranta, Alberto
Abstract: Chromogenic commercial pigments belonging to different classes of smart materials (photochromic and thermochromic) were selected from commercially available examples: a photochromic pigment, able to change from colorless to purple when radiated with UV light; a thermochromic pigment, changing from red to colorless above 31 °C, and a thermochromic changing from orange to yellow above 28 °C. All the pigments were produced by SFXC. They were chemically analyzed using SEM, EDXS and FTIR in order to understand their composition and the mechanisms responsible for their chromogenic behavior. Their behavior was studied by triggering the color transitions. The pigments were introduced in an epoxy binder to produce smart paints. The optical properties of the so produced coatings were analyzed using a spectrophotometer, with an emphasis on their reflectance, absorption and emission spectra. Their color was studied in different working conditions, inducing the transitions responsible for their smart behavior. The samples were subjected to different degrees of degradation using a UV-B chamber, in order to simulate with an accelerated test, the exposure to several days of sunlight and heat. The data collected in the various conditions were compared and discussed, with particular focus on their performances after prolonged usage and their eligibility for practical everyday use. The smart coatings that were produced are still able to display their chameleonic behavior at the end of the UV-B degradation time, which lasted for 500 h. The pigments partially degrade, as the color transition becomes attenuated. The epoxy binder also degrades and its yellowing partially compromises the chromatic behavior. However, it is able to protect the pigments from further degradation and concurs to guarantee the functionality of the system. Graphical abstract: Image 1 Highlights: Chromogenic pigments permit to have smart organic coatings. Natural weathering could damage the pigments reducing the effect. Changing color paints are useful in several applications. Synergic effect between pigments and polymeric matrix is shown.